Children as Victims and Objects of Crime: A Criminological Analysis of Economic Exploitation in Urban Environments - Indah Sri Utari (Semarang State University Undergraduate Law and Society Review, 2025)
Economic exploitation of children in urban environments is a complex form of social crime that is often hidden behind the dynamics of city life. Children are not only victims of family economic pressures, but also become objects of crime by parties who take advantage of their vulnerability. This article aims to analyze the phenomenon of child exploitation from a criminological perspective, highlighting how social structures, economic inequality, and weak legal protection systems contribute to the rampant practice of exploitation in urban areas. Using a qualitative approach and critical criminology theory, this study examines the patterns of exploitation that occur, including the involvement of children in informal work, forced labor, and other forms of hidden exploitation. The results of the analysis show that child exploitation is not only triggered by economic factors, but also by the cultural normalization of child labor, lack of legal awareness at the community level, and minimal community-based state intervention. This article emphasizes that child exploitation must be understood as a structural crime that requires an interdisciplinary and collaborative approach. Prevention and handling efforts are not enough only through law enforcement, but also through community empowerment, social policy reform, and strengthening child protection systems that are responsive to the urban context. Thus, protecting children from economic exploitation must be a priority agenda in criminal and social policies in urban areas.